Physicochemical evaluation of chicken liver enriched sausages for maternal nutrition and stunting prevention - Pratiwi, Yunita Satya; Rosida,; Sari, Puspita; Maulidi, Nadien Mutia Intan; Ramadhani, Gina Salsabila (Journal of Food Technology Research, 2025)
Stunting is a condition of chronic malnutrition resulting from prolonged inadequate nutritional intake, particularly during early childhood. A contributing factor is maternal malnutrition during pregnancy, including chronic energy deficiency and anemia. Therefore, this study aimed to formulate and analyze the physicochemical, microbiological, and organoleptic characteristics of chicken meat sausages enriched with chicken liver, kidney beans, skim milk, and carrageenan. These ingredients were selected for their high nutritional value, particularly heme iron, which is more bioavailable and may contribute to reducing stunting risk. In addition, the organoleptic test results of sausages showed a significant difference in the sensory test of sausages with a p-value <0.05. The optimal formulation was identified as treatment A3K1 (chicken liver 32.5: kidney beans 17.5: skim milk 15: carrageenan 1). The proximate analysis for formula A3K1 included ash content of 3.11%, moisture 55.31%, calories 199.35 kcal, protein 18.81%, carbohydrates 16.16%, fat 6.61%, iron 9.27%, and calcium 45.25%. In the chemical test, significant results were obtained with a p-value < 0.05. The chewiness ranged from 722.57 to 1175.32 gf, water holding capacity (WHC) between 1.41 and 2.37%, and cooking loss from 4.69 to 4.75%. While had a significant effect with a p-value <0.05. Microbiological analysis confirmed the absence of Escherichia coli and Salmonella spp among all samples. The inclusion of chicken liver, kidney beans, skim milk, and carrageenan significantly enhanced the physicochemical properties and nutritional profile of the sausages, indicating its potential to support maternal nutrition and contribute to stunting prevention strategies.